الاغتراب الثقافي في الدستور العراقي: دراسة لسانية أنثروبولوجية - التميمي، جواد كاظم (Natural Sciences Publishing, 2019)
Standing Constitution means of people's instruments to consolidation principle social development contract and organization main general lines to form the government. The Iraqis had gotten on their standing constitution after the end temporary constitution period that long- term. In 2003, but there was a big problem in the way their treat seriously with constitution. Texts which incarnate that the Iraqis don't have experience in the constitutions, because the constitution is new culture structure on the Iraqis through the American occupation and appearance the globalization. This studying showed the constitution's problem from where it considered modern text through theory side. Indicative content convicted Iraqi culture constructions which had hardcore anthropology oriented of realism side. Go ahead this case to failure to reach living to gather moment, which means the social development contract among the Iraqis. From this aspect, we understant that the Iraqis between them and the living together moment long distance of controversy history.
الدستور الدائم يعني أدوات الشعب لتعزيز مبدأ عقد التنمية الاجتماعية وتنظيم الخطوط العامة الرئيسية لتشكيل الحكومة. لقد حصل العراقيون على دستورهم الدائم بعد انتهاء فترة الدستور المؤقت على المدى الطويل. في عام 2003، ولكن كانت هناك مشكلة كبيرة في طريقة تعاملهم بجدية مع الدستور. النصوص التي تجسد أن العراقيين ليس لديهم خبرة في الدساتير، لأن الدستور هو بنية ثقافية جديدة على العراقيين من خلال الاحتلال الأمريكي ومظهر العولمة. أظهرت هذه الدراسة مشكلة الدستور في أنها نظرت إلى النص الحديث من خلال الجانب النظري. المحتوى الدلالي يدين المنشآت الثقافية العراقية التي تحتوي على الأنثربولوجين المتشددين بمواجهة جانب الواقعية. المضي قدما في هذه القضية أدى إلى الفشل في التعايش معا، وهو ما يعني عقد التنمية الاجتماعية بين العراقيين، من هذا الجانب، ندرك أن العراقيين بينهم وبين الذين يعيشون معهم يحظون تاريخ طويل من الجدل.
Keywords: العراق -- القوانين والتشريعات -- الاغتراب الثقافي -- اللسانيات -- الأنثروبولوجيا